2020
DOI: 10.1111/ctr.14187
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain post–heart transplantation is associated with an increased risk for allograft vasculopathy and rejection

Abstract: OBJECTIVE Obesity and overweight are associated with an increased risk for cardiovascular disease. Since fat mass (FM) and fat‐free mass (FFM) both contribute to total body weight (TBW), we characterized the post–heart transplantation (HT) change in TBW and its implications for outcomes. METHODS Post‐HT changes in TBW, FM, and FFM were reviewed for 211 HT patients assessed during 1997–2017. Endpoints included cardiac allograft vasculopathy (CAV) and rejection. RESULTS Median TBW increased by 7.3% at 1 year, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A study of 59 Norwegian HTRs observed a relatively stable total lean mass with a small total fat mass increase (26%-28%), 19 consistent with the majority of HTRs living a sedentary lifestyle, 19,20 and weight gain more likely due to increased fat. 19,[21][22][23] Our findings regarding serum total cholesterol are consistent with previous observations that the highest increases also occur in the first 12 months, 12,13 though others have observed a further increase in cholesterol levels after 12 months, and a Brazilian study of 82…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A study of 59 Norwegian HTRs observed a relatively stable total lean mass with a small total fat mass increase (26%-28%), 19 consistent with the majority of HTRs living a sedentary lifestyle, 19,20 and weight gain more likely due to increased fat. 19,[21][22][23] Our findings regarding serum total cholesterol are consistent with previous observations that the highest increases also occur in the first 12 months, 12,13 though others have observed a further increase in cholesterol levels after 12 months, and a Brazilian study of 82…”
Section: Discussionsupporting
confidence: 91%
“…Weight gain in HTRs may be due partly to increased lean mass due to increased physical activity after transplantation; we could not distinguish an increase in fat from lean mass. A study of 59 Norwegian HTRs observed a relatively stable total lean mass with a small total fat mass increase (26%–28%), 19 consistent with the majority of HTRs living a sedentary lifestyle, 19,20 and weight gain more likely due to increased fat 19,21‐23 …”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, another recent study showed that the weight gain in recipients after heart transplantation could increase the risk for allograft vasculopathy and rejection, suggesting the impact of obesity on outcomes of heart transplantation [109].…”
Section: Referencesmentioning
confidence: 99%